"White" Guadeloupeans of "Mixed" Ancestry: Complicating Analyses of Whiteness and White Supremacy. Issue 2 (1st June 2021) - Gordien, Ary
Abstract: This article explores the various ways in which Guadeloupeans of mixed African and European ancestry who are perceived as White self-identify in relation to their family and individual trajectories. This partial analysis is based on half-dozen semistructured interviews carried out in the course of researching nationalism, race, and ethnicity in Guadeloupe. Complicating rigid definitions of Whiteness and White supremacy, this article interprets the intricate meanings of Whiteness in the specific context of Guadeloupe, and its complex articulation with material and symbolic privilege.